Bread Culture in Peasants of Starobelsky District of Kharkiv Province (Based on the Collection of V. Ivanov «Life and Art of Peasants of Kharkiv Province ») - Боряк, Олена (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with a complex of rituals and beliefs connected with bread on the basis of folklore and ethnographic material recorded at the end of the XIX century in several settlements of Starobilsky district of Kharkiv province. The culture of bread is an optimal object to create a socio-cultural portrait of a separate territory. Besides, ethnic identity is also reflected in the elements of material culture. Given material is a vivid evidence of the uniqueness of spiritual and worldview values of the community that inhabited the land of Slobids’ka Ukraine.